2016
DOI: 10.1007/s12665-016-5249-6
|View full text |Cite
|
Sign up to set email alerts
|

Sorption behavior of dodecylbenzene sulfonic acid on humic acids from Mollisol and Alluvial soils

Abstract: Dodecylbenzene sulfonic acid (DBSA), the acid form of sodium dodecylbenzenesulfonate (SDBS), is often identified and detected in soils. However, it still has less awareness of the sorption behavior of DBSA with soil organic matter. In this paper, the sorption behaviors of DBSA on two different types of soils (Mollisol and Alluvial soils) and soil humic acids (HAs) were studied and compared, and the mechanisms of HAs and DBSA interactions were discussed. Sorption dynamics and isotherms were studied using the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The results indicated that the adsorption of DBSA on C700, P300, and P700 was relatively slow. However, it was faster than the adsorption of DBSA on soils and Mollisol soil HA [ 17 ]. Within 5 h of solution/biochar contact, 89.67%, 78.34%, and 83.09% of the initial DBSA amount were removed by C700, P300, and P700, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the adsorption of DBSA on C700, P300, and P700 was relatively slow. However, it was faster than the adsorption of DBSA on soils and Mollisol soil HA [ 17 ]. Within 5 h of solution/biochar contact, 89.67%, 78.34%, and 83.09% of the initial DBSA amount were removed by C700, P300, and P700, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…DBSA could be adsorbed on humic acids (HAs) by H bonds, hydrophobic interactions, and electron donor-acceptor mechanisms. Alluvial soil HA had a higher sorption capacity than that of Mollisol soil HA [ 17 ]. The adsorption behaviors of DBSA on biochars have been seldom reported.…”
Section: Introductionmentioning
confidence: 99%